Defensive Weapons and Star Wars: A Supergame with Optimal Punishments - Giampiero Giacomello; Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
We model the perspective faced by nuclear powers involved in a supergame where nuclear deterrence is used to stabilise peace. This setting allows us to investigate the bearings of defensive weapons on the effectiveness of deterrence and peace stability, relying on one-shot optimal punishments. We find that the sustainability of peace is unaffected by defensive shields if both countries have them, while a unilateral endowment of such weapons has destabilising consequences.
Keywords: C73; F51; 330